2010
DOI: 10.1016/j.nuclphysa.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Charged-particle thermonuclear reaction rates: II. Tables and graphs of reaction rates and probability density functions

Abstract: Numerical values of charged-particle thermonuclear reaction rates for nuclei in the A=14 to 40 region are tabulated. The results are obtained using a method, based on Monte Carlo techniques, that has been described in the preceding paper of this series (Paper I). We present a low rate, median rate and high rate which correspond to the 0.16, 0.50 and 0.84 quantiles, respectively, of the cumulative reaction rate distribution. The meaning of these quantities is in general different from the commonly reported, but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
468
20
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(521 citation statements)
references
References 252 publications
(453 reference statements)
28
468
20
5
Order By: Relevance
“…However, even the lowest value we find (−0.90) is still higher than the observations (down to −2 dex). Cavanna et al (2015) reported a revised value of the 22 Ne(p,γ) 23 Na rate measured underground, however, at the temperature of interest (< 20 MK) the new rate is the same as the rate we have used here (Iliadis et al 2010). On the other hand, the rate of the destruction reaction 23 Na(p,α) 20 Ne is poorly known (Iliadis et al 2010).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, even the lowest value we find (−0.90) is still higher than the observations (down to −2 dex). Cavanna et al (2015) reported a revised value of the 22 Ne(p,γ) 23 Na rate measured underground, however, at the temperature of interest (< 20 MK) the new rate is the same as the rate we have used here (Iliadis et al 2010). On the other hand, the rate of the destruction reaction 23 Na(p,α) 20 Ne is poorly known (Iliadis et al 2010).…”
Section: Discussionmentioning
confidence: 74%
“…Nuclear reaction rates were included using the reaclib file provided by the Joint Institute for Nuclear Astrophysics (JINA, Cyburt et al 2010), as of May 2012 (reaclib V2.0). The rates of the neutron source reactions correspond to Heil et al (2008) for the 13 C(α,n) 16 O and to Iliadis et al (2010) for the 22 Ne(α,n) 25 Mg and 22 Ne(α,γ) 26 Mg reactions. For the neutron-capture cross sections, the JINA reaclib database includes the KADoNiS database (Dillmann et al 2006) 2 .…”
Section: The Stellar Nucleosynthesis Sequencesmentioning
confidence: 99%
“…The usdb-cdpn present rate divided by the rate given in the 2010 evaluation (Table B.58 of [8]) is shown in Fig. (5).…”
Section: Uncertainties In the Resonant Capture Reaction Ratesmentioning
confidence: 99%
“…The strengths of the resonances at E p = 45 and 70 keV are too low to be measured directly due to the Coulomb barrier but have been included in the calculation of the reaction rate derived from Ref. [28], based on the ( 3 He,d) spectroscopic factors of Ref [19].…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Thanks to evaporated protective layers [27], the targets exhibited little to no degradation over ∼ 20 C of bombardment. Using mainly the strengths and energies obtained in this work together with supplemental information from other work [24,28], we have re-evaluated the thermonuclear reaction rate of 22 Na(p, γ), and full hydrodynamic simulations have been performed to estimate the effect of the new rate on the flux of 22 Na from novae. This article is a detailed presentation of our experiment, its results, and their implications, complementing our previous reports [29,30].…”
mentioning
confidence: 99%